2015
DOI: 10.3233/bmr-140581
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent anterior cruciate ligament reconstruction surgery and optimal duration of supervised physiotherapy

Abstract: A 22-year-old patient undergoing unilateral surgical reconstruction of the anterior cruciate ligament (ACL) of the right knee volunteered for the research project and followed an established contemporary hospital-based rehabilitation programme. The patient was supervised post-surgically by an experienced and clinically specialized physiotherapist. The clinical outcomes of rehabilitation were assessed by selected validated patient-reported and objectively-measured outcomes of functional performance capability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…appointments (av/week) Supervision category Intervention period (months) OM assessment (months) OMs n Age (mean) Sex Graft Activity level Beard and Dodd (1998) [ 31 ] RCT 31 28 M 21 F 5 BPTB Not stated Home: not specified Clinic + knee class: 16 (1.33) Unspecified High Mid (approx. 1-4) Pre-operative, 3 and 6 Lysholm knee score, IKDC knee evaluation form, Modified Tegner activity score, VAS sports frequency and level, VAS ADLs, Isokinetic Fl and ext (60deg/sec), KT-1000 Christensen et al (2018) [ 32 ] Retrospective 332 31.2 M 192 F 140 HS / BPTB Not stated Unsupervised: 3–7 (0.16) Semi-supervised: 8–13 (0.33) Supervised: 14–35 (0.76) Low Mod High Late (0-8) 8 KOS-ADL, NPRS Darian et al (2015) [ 33 ] Case report 1 22 M HS Competitive sport Supervised: 15 (0.63) High Mid (0-6) Pre-operative, 1.5, 3 and 6 IKDC subjective knee evaluation, Lysholm knee score, KOOS, K-SES, single hop De Carlo and Sell (1997) [ 34 ] Retrospective 180 26.8 M 130 F 50 BPTB Sport participation (100%) Home: 7 (0.29) Standard routine: 20 (0.83) Low High Mid (0-6) 1,6 and 12 Isokinetic Fl and ext (180deg/s) ROM, Modified Noyes Questionnaire Dempsey et al (2019) [ 30 ] Cross-sectional 60 29.7 M 31 F 29 …”
Section: Category (A) Rehabilitation Prescription and Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…appointments (av/week) Supervision category Intervention period (months) OM assessment (months) OMs n Age (mean) Sex Graft Activity level Beard and Dodd (1998) [ 31 ] RCT 31 28 M 21 F 5 BPTB Not stated Home: not specified Clinic + knee class: 16 (1.33) Unspecified High Mid (approx. 1-4) Pre-operative, 3 and 6 Lysholm knee score, IKDC knee evaluation form, Modified Tegner activity score, VAS sports frequency and level, VAS ADLs, Isokinetic Fl and ext (60deg/sec), KT-1000 Christensen et al (2018) [ 32 ] Retrospective 332 31.2 M 192 F 140 HS / BPTB Not stated Unsupervised: 3–7 (0.16) Semi-supervised: 8–13 (0.33) Supervised: 14–35 (0.76) Low Mod High Late (0-8) 8 KOS-ADL, NPRS Darian et al (2015) [ 33 ] Case report 1 22 M HS Competitive sport Supervised: 15 (0.63) High Mid (0-6) Pre-operative, 1.5, 3 and 6 IKDC subjective knee evaluation, Lysholm knee score, KOOS, K-SES, single hop De Carlo and Sell (1997) [ 34 ] Retrospective 180 26.8 M 130 F 50 BPTB Sport participation (100%) Home: 7 (0.29) Standard routine: 20 (0.83) Low High Mid (0-6) 1,6 and 12 Isokinetic Fl and ext (180deg/s) ROM, Modified Noyes Questionnaire Dempsey et al (2019) [ 30 ] Cross-sectional 60 29.7 M 31 F 29 …”
Section: Category (A) Rehabilitation Prescription and Participationmentioning
confidence: 99%
“…Outcome measure use was investigated by grouping the type of OM into the following categories: hop tests, isokinetic dynamometry, patient reported OMs, clinical-based OMs and other OMs. The number of studies in each category were as follows; five studies used at least one hop test [ 30 , 33 , 36 , 40 , 46 ], eight studies used an isokinetic dynamometry strength measure [ 30 , 31 , 34 , 37 , 38 , 40 , 42 , 45 ] and 18 different patient-reported OMs were utilised in 12 different studies [ 30 , 32 – 39 , 43 , 44 , 46 ]. Eighteen different clinical-based assessments (pain, range of motion, atrophy, effusion, laxity, Lysholm knee score, Tegner activity scale and international knee documentation committee knee evaluation) were used in 15 studies [ 31 38 , 40 , 43 48 ] and 14 other OMs (RTS status/activity level, re-rupture, gait analysis, functional movement screen, surgery satisfaction, imaging and demographics) were utilised in 10 studies [ 38 , 39 , 41 – 44 , 46 49 ].…”
Section: Category (A) Rehabilitation Prescription and Participationmentioning
confidence: 99%
“…. Another study has marked that the patient needs 15 physical therapy visits during the first 6 weeks post-surgery [28]. Also, many studies pointed out the importance of the physical therapists' supervision and follow up on the home exercise programs rather than decreasing the number of total visits.…”
Section: Injury-surgery Period and Functional Resultsmentioning
confidence: 99%
“…However, the obvious advantages of rehabilitation programmes delivered in well-controlled environment over rehabilitation programmes self-managed by the patients in community have been reported in clinical trials carried out on ACL reconstruction indicating the significant role of supervision. Despite the latter fact, a uniform rehabilitation programme following ACL reconstruction was not reported in the literature [31]. This issue was observed while carrying out this review and only few studies were found where supervision was discussed.…”
mentioning
confidence: 95%
“…In contrast, Fischer et al [28], Feller et al [29], De Carlo et al [30] and Hohmann et al [22] associated supervision with the number of physiotherapy sessions received by the patients in hospital or other clinical settings included clinics. In a case report by Darain et al [31], su-pervision during rehabilitation was associated with the quality time received by a patient from monitoring of physiotherapist in a hospital. Volumes and intensities of training during rehabilitation following ACL reconstruction had not received robust attention and none of the trials included in this review had associated these characteristics with supervision.…”
mentioning
confidence: 98%